Comparison between flapless and open-flap implant placement: a systematic review and meta-analysis - Lemos, C. A.A. [UNESP]; Verri, F. R. [UNESP]; Cruz, R. S. [UNESP]; Gomes, J. M.L. [UNESP]; dos Santos, D. M. [UNESP]; Goiato, M. C. [UNESP]; Pellizzer, E. P. [UNESP] (Elsevier, 2018)
No consensus has been reached regarding the influence of the flapless and open-flap surgical techniques on the placement of dental implants. This systematic review compared the effects of flapless implant placement and implant placement with elevation of the mucoperiosteal flap in terms of marginal bone loss, implant survival rate and complications rates. This review followed PRISMA guidelines and was registered in PROSPERO with the registration number CRD42017071475. Two independent reviewers performed a comprehensive search of the PubMed/MEDLINE, Scopus, and Cochrane Library databases for studies published until December 2017. The search identified 559 references. After a detailed review, 24 studies were assessed for eligibility. A total of 1025 patients who had received a total of 1873 dental implants were included. There were no significant differences between the flapless and open-flap surgical techniques in terms of implant survival rates (P = 0.34; risk ratio (RR): 1.36; confidence interval (CI): 0.72–2.56), marginal bone loss (P = 0.23; MD: −0.20; CI: −0.52–0.13), or complication rates (P = 0.67; RR: 1.10; CI: 0.70–1.73). The current meta-analysis showed that the implant survival rate, marginal bone levels, and complications of flapless surgery were similar to those of open-flap surgery over a mean follow-up period of 21.62 months.
Keywords: dental implant; flapless; full thickness; surgical approach; systematic review